The first Normal School for Nursery-School Teachers in Guatemala - Cortez Sic, José Enrique; Crispín López, Haydee Lucrecia; Hori Herrera, Angela Kiku (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: To analyze the historical development of the first Normal School for nursery-school teachers, created in 1928 in the capital city of Guatemala, as the main institution for the training of pre-school teachers at the national level. Originality/contribution: this research process follows the historical line and seeks to make visible the different stages of formative development, as an experience. Emphasis is placed on curricular evolution and on the importance of providing continuity to quality training for pre-school teachers. The history of Normal Schools in Guatemala dates back to 1875 with the beginning of the Central Normal School for Men. Subsequently, others were created that contributed to the training of teachers, especially the one that is the subject of today's research: the Escuela Normal para Maestras de Párvulos "Dr. Alfredo Carrillo Ramírez", the first educational institution of its kind since 1928. Method: the qualitative method was followed through documentary review of primary and hemerographic sources, as well as an interview with a person in a managerial position who has been in charge of teaching and administrative tasks in this educational institution. Strategies/information collection: we proceeded to the review of unpublished documents and bibliography related to the history of education in Guatemala, and basic information on the events of the Normal School since 1928. Likewise, we structured an instrument for the application of the interview with the management personnel based on semi-structured questions. Conclusions: The first Normal School for Nursery-School Teachers has been an experiential stronghold in the Guatemalan educational system. Its contributions are valuable examples in teacher training and have favored the expansion of coverage for the care of children at the pre-primary level.